2014
DOI: 10.1007/s00268-014-2557-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function and Body Image are Similar after Laparoscopy‐Assisted and Open Ileal Pouch–Anal Anastomosis

Abstract: Although there might be a tendency toward better body image among laparoscopy-treated women, the two surgical techniques seem equal with respect to postoperative sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
1
18
1
1
Order By: Relevance
“…Additionally, surgeons should bear in mind that young patients are socially active, so great efforts should be made to preserve postoperative sexual, urinary, and anal function. However, previous studies have reported that impaired function after TPC-IPAA, mainly due to autonomic nerve injury and poor pouch function, is not uncommon [43][44][45]. The present study demonstrated 99 % sphincter preservation with an excellent Wexner score after laparoscopic TPC-IPAA.…”
Section: Discussioncontrasting
confidence: 42%
“…Additionally, surgeons should bear in mind that young patients are socially active, so great efforts should be made to preserve postoperative sexual, urinary, and anal function. However, previous studies have reported that impaired function after TPC-IPAA, mainly due to autonomic nerve injury and poor pouch function, is not uncommon [43][44][45]. The present study demonstrated 99 % sphincter preservation with an excellent Wexner score after laparoscopic TPC-IPAA.…”
Section: Discussioncontrasting
confidence: 42%
“…For example, body image scores tend to be higher in patients following laparoscopic versus open procedures and in non-operated versus operated patients, though these differences are typically found only in women. 3,42,43,49 These gender differences may persistent for many years post-surgery, particularly in patients who undergo open surgery. 43 Conversely, some studies have found no differences in body image or ratings of incision scars among men and women post-surgery.…”
Section: Resultsmentioning
confidence: 99%
“…16,47,51 Indeed, other studies have found even increased post-operative levels of sexual impairment among women, including increased dyspareunia, 15,16,51 decreased libido, 15 and problems with lubrication. 15,26 In fact dyspareunia is commonly reported among patients following IPAA, 16,38,46,49,53,67 with rates as high as 30%. 46 However, the majority of these studies did not include preoperative assessments of sexual functioning, making it difficult to interpret results of post-operative sexual functioning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, laparoscopic surgery has been used in an increasing proportion of patients undergoing IPAA or IRA (IPAA: 23-53%; IRA: 58-62%) [61][62][63][64] . According to previously published reports, laparoscopic surgery takes a longer time, but there are no differences between laparoscopic and open surgery in the incidence of postoperative complications, mortality, reoperation rate or readmission rate 63) ; furthermore, the laparoscopic approach yields better esthetic outcomes with less intraoperative bleeding.…”
Section: Cq6: Is Laparoscopic Surgery Useful For Fap?mentioning
confidence: 99%